Ethnic differences in cross‐sectional associations between impaired glucose regulation, identified by oral glucose tolerance test or HbA1c values, and cardiovascular disease in a cohort of European and South Asian origin. Issue 3 (19th October 2015) - Eastwood, S. V.; Tillin, T.; Mayet, J.; Shibata, D. K.; Wright, A.; Heasman, J.; Beauchamp, N.; Forouhi, N. G.; Hughes, A. D.; Chaturvedi, N.
Abstract: Aims: We contrasted impaired glucose regulation (prediabetes) prevalence, defined according to oral glucose tolerance test or HbA1c values, and studied cross‐sectional associations between prediabetes and subclinical/clinical cardiovascular disease (CVD) in a cohort of European and South Asian origin. Methods: For 682 European and 520 South Asian men and women, aged 58–85 years, glycaemic status was determined by oral glucose tolerance test or HbA1c thresholds. Questionnaires, record review, coronary artery calcification scores and cerebral magnetic resonance imaging established clinical plus subclinical coronary heart and cerebrovascular disease. Results: Prediabetes was more prevalent in South Asian participants when defined by HbA1c rather than by oral glucose tolerance test criteria. Accounting for age, sex, smoking, systolic blood pressure, triglycerides and waist–hip ratio, prediabetes was associated with coronary heart disease and cerebrovascular disease in European participants, most obviously when defined by HbA1c rather than by oral glucose tolerance test [odds ratios for HbA1c ‐defined prediabetes 1.60 (95% CI 1.07, 2.39) for coronary heart disease and 1.57 (95% CI 1.00, 2.51) for cerebrovascular disease]. By contrast, non‐significant associations were present between oral glucose tolerance test‐defined prediabetes only and coronary heart disease [odds ratio 1.41 (95% CI 0.84, 2.36)] and HbA1c ‐defined prediabetes only and cerebrovascular disease [odds ratio 1.39 (95% CI 0.69, 2.78)] in South Asian participants. Prediabetes defined by HbA1c or oral glucose tolerance test criteria was associated with cardiovascular disease (defined as coronary heart and/or cerebrovascular disease) in Europeans [odds ratio 1.95 (95% CI 1.31, 2.91) for HbA1c prediabetes criteria] but not in South Asian participants [odds ratio 1.00 (95% CI 0.62, 2.66); ethnicity interaction P = 0.04]. Conclusions: Prediabetes appeared to be less associated with cardiovascular disease in the South Asian than in the European group. These findings have implications for screening, and early cardiovascular prevention strategies in South Asian populations. What's new?: For participants of European origin, HbA1c values defined as impaired glucose regulation (prediabetes) were cross‐sectionally associated with coronary heart disease, cerebrovascular disease and the composite outcome of cardiovascular disease. By contrast, in South Asian participants prediabetes defined according to HbA1c concentration was non‐significantly associated with cerebrovascular disease only, and associations between HbA1c concentration‐defined prediabetes and overall cardiovascular disease were absent and, thus significantly weaker, than those seen in the European participants. This suggests that current prediabetes HbA1c thresholds may be inappropriate in South Asian groups as prediabetes defined in this way did not appear to confer excess cardiovascular risk in this ethnic group.